A new photoacoustic method based on the modulation of the light induced absorption coefficient. (14th March 2016) - Engel, S; Wenisch, C; Müller, F A; Gräf, S
Abstract: The present study reports on a new photoacoustic (PA) measurement method that is suitable for the investigation of light induced absorption effects including e.g. excited state absorption. Contrary to the modulation of the radiation intensity used in conventional PA-methods, the key principle of this novel setup is based on the modulation of the induced absorption coefficient by light. For this purpose, a pump-probe setup with a pulsed pump laser beam and a continuous probe laser beam is utilized. In this regime, the potential influence of heat on the PA-signal is much smaller when compared to arrangements with pulsed probe beam and continuous pump beam. Beyond that, the negative effect of thermal lenses can be neglected. Thus, the measurement technique is well-suited for materials exhibiting a strong absorption at the pump wavelength. The quantitative analysis of the induced absorption coefficient was achieved by the calibration of the additional PA-signal caused by the continuous probe laser to the PA-signal resulting from the pulsed pump laser using thallium bromoiodide (KRS-5) as sample material.